(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2022)
The main objective of this article is to analyze how mediation is inserted in the guiding documents of the Judicial Policy for the Adequate Treatment of conflicts of interest, and to reflect on the formation and performance of the judicial mediator. The approach to the theme starts from a synthesis of the main guidelines, emphasizing aspects of mediator training, briefly contextualizing the crisis of the judiciary, which led to the adoption of consensual methods of conflict resolution, to then analyze different aspects of the mediation institute. based on its legal definition, with the expectation of leading to a reflection on the importance of preserving the integrity of mediation as a practice differentiated from other consensual methods of conflict treatment in the judicial system